2011
DOI: 10.1504/ijtamm.2011.043535
|View full text |Cite
|
Sign up to set email alerts
|

Viscous contribution to the pressure for electroviscous potential flow analysis of capillary instability

Abstract: Viscous contribution for the Viscous Potential Flow (VPF) analysis of capillary instability with axial electric field at the interface of two viscous fluids has been analysed. In VPF, viscosity enters through normal stress balance and the effects of shearing stresses are completely ignored. To include the effect of shearing stresses, viscous pressure is included in normal stress balance along with irrotational pressure and it is assumed that the viscous contribution to the irrotational pressure will resolve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Awasthi and Agrawal [21] have studied the viscous potential flow analysis of Kelvin-Helmholtz instability of a cylindrical interface and observed that the viscosity has a stabilizing effect. The viscous potential flow theory has been widely used in recent years, and attracts many researchers to study various linear and nonlinear stability problems of physical interest (Joseph and Liao [22], Joseph et al [23], Wang et al [24], Elcoot [25,26], Sirwah [27], Zakaria [28], Obied Allah [29], Awasthi and Agrawal [30], Awasthi et al [31], Moatimid and Hassan [32], and Asthana et al [33], among others).…”
Section: Introductionmentioning
confidence: 99%
“…Awasthi and Agrawal [21] have studied the viscous potential flow analysis of Kelvin-Helmholtz instability of a cylindrical interface and observed that the viscosity has a stabilizing effect. The viscous potential flow theory has been widely used in recent years, and attracts many researchers to study various linear and nonlinear stability problems of physical interest (Joseph and Liao [22], Joseph et al [23], Wang et al [24], Elcoot [25,26], Sirwah [27], Zakaria [28], Obied Allah [29], Awasthi and Agrawal [30], Awasthi et al [31], Moatimid and Hassan [32], and Asthana et al [33], among others).…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the axial electric field has a stabilizing effect, while the radial one has a dual rule (stabilizing and destabilizing) on the system's stability. Awasthi and Agrawal [17] presented an analysis of the capillary instability of electroviscous potential flow. Then, they revisited the analysis in their study of [18] as they analysed the capillary instability with radial electric field of viscous potential flow.…”
Section: Introductionmentioning
confidence: 99%
“…where P is the pressure and E t and E n are the tangential and normal components of the electric field, respectively. Integrating the linear equation of motion (1) results in Bernoulli's formula; eliminating the pressure using Bernoulli equation, condition (17) can be rewritten in linearized form as…”
mentioning
confidence: 99%
“…Recently, Awasthi and Agrawal [2011] have studied the viscous contribution to the pressure for the potential flow analysis of Kelvin-Helmholtz instability in the presence of tangential magnetic field and observed that the inclusion of irrotational shearing stresses stabilize the system. The viscous contribution to the pressure for the potential flow analysis of capillary instability in the presence of axial electric field has been studied by Awasthi and Agrawal [2011].…”
Section: Introductionmentioning
confidence: 99%
“…The viscous contribution to the pressure for the potential flow analysis of capillary instability in the presence of axial electric field has been studied by Awasthi and Agrawal [2011]. They have observed that the axial electric field and irrotational shearing stresses both have stabilizing effect on the stability of the system.…”
Section: Introductionmentioning
confidence: 99%